2023
DOI: 10.3390/cancers15102790
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Calcium Supplement Use and High-Risk Breast Cancer: A Case–Control Study among BRCA1 and BRCA2 Mutation Carriers

Abstract: The role of vitamin D and calcium use in the development of breast cancer among women in the general population is not clear. Furthermore, whether vitamin D and calcium supplement use are associated with breast cancer in high-risk populations has not been evaluated. Thus, we evaluated the association between vitamin D and/or calcium supplement use and breast cancer among women with a pathogenic variant (mutation) in BRCA1 or BRCA2. BRCA mutation carriers enrolled in a longitudinal study were invited to complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Studies addressing CaD supplementation in the context of BC prevention are indeed scarce. Most articles in the scientific literature focus on the study of supplementation of both factors separately [ 117 , 118 ], so combined CaD supplementation and its association with BC risk require further research.…”
Section: Resultsmentioning
confidence: 99%
“…Studies addressing CaD supplementation in the context of BC prevention are indeed scarce. Most articles in the scientific literature focus on the study of supplementation of both factors separately [ 117 , 118 ], so combined CaD supplementation and its association with BC risk require further research.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that our cancer group could have been better self-educated and made attempts at healthier nutrition, regardless of the fact that such behaviors do not act as prophylaxis at that stage of the disease. Guyonnet et al reported that an increased intake of vitamin D and calcium lowered the risk of developing breast cancer, mainly among the carriers of the BRCA1 gene [ 42 ]. It has also been demonstrated that higher consumption of essential amino acids, which are mainly found in dairy products—leucine, isoleucine, and valine—is associated with longer survival among breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%